2009
DOI: 10.1038/cgt.2009.65
|View full text |Cite
|
Sign up to set email alerts
|

An HDAC inhibitor enhances the antitumor activity of a CMV promoter-driven DNA vaccine

Abstract: The cytomegalovirus (CMV) promoter is considered to be one of the strongest promoters for driving the in vivo expression of genes encoded by DNA vaccines. However, the efficacy of DNA vaccines has so far been disappointing (particularly in humans), and this might be explained in part by histone deacetylase (HDAC)-mediated chromatin condensation. Hence, we sought to investigate whether increasing the expression of DNA vaccine antigens with the HDAC inhibitor OSU-HDAC42 would enhance the efficacy of DNA vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…HDACi-mediated enhancement of transgene expression from the CMV promoter would be beneficial not only for viral gene therapy but also for nonviral approaches. For example, recent studies demonstrated that HDACi enhanced the efficacy of a CMV-driven DNA vaccine and may also improve polymer-mediated gene delivery [16, 17]. Interestingly, HDACi inhibited gene expression from a prostate-specific promoter, indicating that combination of these drugs with tissue-specific promoters needs to be carefully evaluated [18].…”
Section: Resultsmentioning
confidence: 99%
“…HDACi-mediated enhancement of transgene expression from the CMV promoter would be beneficial not only for viral gene therapy but also for nonviral approaches. For example, recent studies demonstrated that HDACi enhanced the efficacy of a CMV-driven DNA vaccine and may also improve polymer-mediated gene delivery [16, 17]. Interestingly, HDACi inhibited gene expression from a prostate-specific promoter, indicating that combination of these drugs with tissue-specific promoters needs to be carefully evaluated [18].…”
Section: Resultsmentioning
confidence: 99%
“…Together, these findings strongly suggest that the successful elimination of HIV-1-infected cells during latency-reversing treatment depends on host immune responses that kill cells in which viral gene expression is reactivated. Interestingly, experience from preclinical and clinical studies with HDACi in the context of oncologic diseases similarly indicates that elimination of malignant cells during HDACi therapy critically depends on effective host immune activity (35) and that combinations of HDACi and immune-based interventions may lead to more potent therapeutic effects against cancer cells (45)(46)(47). In the present work, we conducted a detailed and comprehensive analysis of innate and adaptive host immune responses during treatment with the HDACi panobinostat in ART-treated HIV-1-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since transcriptional silencing is associated with HDAC-mediated chromatin condensation, HDAC inhibitors have been reported to influence virus promoter-driven gene expression following DNA vaccination. AR-42 (also known as OSU-HDAC42; ApexBio), a hydroxamate-tethered phenylbutyrate derivative that acts as a pan-HDAC inhibitor, increased the expression of Her-2/neu DNA vaccine and resulted in a greater infiltration of lymphocytes into tumors in mice [68]. HDAC inhibition enhanced antitumor response induced by Her-2/neu DNA vaccine, leading to significant delays in tumor progression and extending the lifespan of these mice.…”
Section: Hdac Inhibitors and Cancer Vaccinesmentioning
confidence: 99%